Effect of Yoga Attitude on Senior Secondary School Students in Chandigarh: A Comparative Study - Kumar, Manish; Sharma , Sunil (International Research Journal of Ayurveda & Yoga, 2024)
Introduction: This study investigates the attitudes of senior secondary school students in Chandigarh towards Yoga, focusing on the impact of an 8-week intervention on their perceptions and well-being. A total of 200 students (100 male and 100 female), aged 15–20, were randomly selected from government schools. The Yoga Attitude Scale by Dr. M. K. Muchhal (2009) was employed to measure attitudes before and after the intervention, classifying them as favorable, moderate, or unfavorable. Methods: A descriptive research method was used, and the intervention involved practicing the Common Yoga Protocol for 45 min, 5 days a week, over 8 weeks. Pre-test and post-test data were analyzed using the “t” test for statistical significance. Results: The findings revealed a significant improvement in attitudes toward Yoga. Male students’ favorable attitudes increased by 7% (from 55% to 62%), while female students showed an 11% increase (from 50% to 61%). The reduction in unfavorable attitudes was more prominent among females, with a 13% decline compared to a minor reduction for males. The mean scores for males rose from 38.755 to 45.087, and for females, from 33.091 to 42.331. Discussion: The results demonstrate that Yoga can positively influence adolescents’ perceptions, with female students showing a stronger response to the intervention. These findings suggest that integrating Yoga into school curricula could promote well-being and help manage academic stress. Conclusion: The results clearly indicate that both groups showed a positive shift in their attitudes post intervention. The intervention proved effective, as a shift from moderate to favorable attitudes was observed Education serves as a cornerstone for personal and societal development, fostering growth, understanding, and essential skills among learners. In this dynamic environment, students are increasingly seeking active roles in their educational journeys, yearning for classrooms that encourage open dialogue, inquiry, and collaborative learning. Teachers are thus tasked with creating engaging, clear, and relevant experiences that resonate with students’ lived realities. They are expected to employ various methodologies that cater to diverse learning styles, often incorporating humor and relatable examples to elucidate complex concepts.